Penile Syringoma: Reports and Review of Patients with Syringoma Located on the Penis - Cohen, Philip R. (Matrix Medical Communications, 2013)
Background: Syringoma of the penis is rare. Purpose: This paper describes two men with syringoma of the penis and summarizes the clinical features of previously reported men with this condition. Methods: A 25-year-old African man presented with a nonpruritic flesh-colored papule on the right side of his proximal dorsal penile shaft and a 22-year-old Caucasian man presented with multiple asymptomatic flesh-colored papules on his ventral and lateral penis. Neither man had similar lesions elsewhere or a family member with this condition. Reports of patients with penile syringoma were identified using a medical search engine (PubMed Central) and references included in the published papers on this subject. Results: Microscopic examination of both men’s papules showed syringoma. Including these individuals, syringoma exclusively localized to the penis has only been reported in 11 men. It usually presents as multiple asymptomatic flesh-colored papules on the dorsal penile shaft of men less than 30 years of age. Epithelial-lined cystic spaces containing homogenous eosinophilic material are noted in the fibrotic upper dermis. The papules do not recur following excisional biopsy. Conclusion: Syringoma exclusively located on the penis is extraordinary and has only been reported in 11 men. It presents as a solitary papule or multiple asymptomatic papules on the penile shaft. Microscopic examination shows epithelial structures and eccrine ducts with comma-like tails resembling tadpoles in the fibrotic upper dermis; amorphous pink secretion is often present in the epithelial-lined spaces. Excision of the penile papules not only provides the diagnosis, but also successfully removes the individual lesion without recurrence.